Determining vertical oscillations of front-plow tractor without support wheel. - Nadykto, Volodymyr; Надикто, Володимир Трохимович; Golub, Gennadii; Kyurchev, Volodymyr; Кюрчев, Володимир Миколайович; Tsyvenkova, Nataliya; Petrov, Gennadii; Yarosh, Yaroslav (My University, 2024)
ENG : The object of this study is a tractor with a front plow without a support wheel. One way to avoid the use of ballast is to use front-mounted plows that operate under the "push" mode. As a rule, such plows are equipped with at least one supporting wheel. The presence of the latter complicates the structure of the plow and, of course, affects the degree of vertical load on the steered wheels of the mobile vehicle.\\\\\\\\\ UKR: Об’єктом дослідження є трактор з переднім плугом без опорного колеса. Одним із способів уникнення застосування баласту є використання плугів з передньою навіскою, які працюють в режимі «штовхання». Як правило, такі плуги оснащені хоча б одним опорним колесом. Наявність останнього ускладнює конструкцію плуга і, безумовно, впливає на ступінь вертикального навантаження на керовані колеса мобільного засобу. За допомогою розробленої математичної моделі та відповідних амплітудних і фазових частотних характеристик досліджено динаміку вертикальних коливань передньої осі трактора з фронтальним начіпним плугом без опорного колеса. В якості збурювального впливу розглянуто вертикальні коливання сумарної сили, що діють на трактор з боку плуга. За результатами моделювання збільшення вертикального навантаження передньої осі трактора на 600 кг обумовлює бажане зменшення значення амплітуди та збільшення фази зовнішніх збурень динамічної системи. Чим вища частота коливань збурення, тим більш прийнятними стають ці характеристики. Встановлено, що для покращення реакції досліджуваної динамічної системи на збурення необхідно зменшити коефіцієнт жорсткості шин передніх коліс. На практиці це досягається шляхом регулювання тиску повітря в шинах. Амплітудно-частотні характеристики системи майже не змінюються при збільшенні коефіцієнта демпфування шин передніх коліс трактора в діапазоні від 1 до 3 кН·с/м, тоді як фазово-частотні характеристики покращуються. Особливо це помітно на частотах коливань збурювального впливу в діапазоні 0–10 с-1. Результати можуть бути покладені в основу оцінки ефективності роботи тракторів з переднім плугом без опорного колеса на ґрунтообробних операціях. Така ефективність може бути досягнута за умови практичної реалізації запропонованих у даній роботі рекомендацій щодо вибору конструктивних параметрів шин передніх коліс трактора. With the help of the constructed mathematical model and the corresponding amplitude and phase frequency characteristics, the dynamics of vertical oscillations of the front axle of a tractor with a front mounted plow without a support wheel were investigated. Vertical fluctuations of the total force acting on the tractor from the side of the plow were considered as a disturbing influence. According to the simulation results, an increase in the vertical load of the front axle of the tractor by 600 kg causes a desired decrease in the value of the amplitude and an increase in the phase of external disturbances of the dynamic system. The higher the frequency of disturbance oscillations, the more acceptable these characteristics become. It was established that in order to improve the response of the studied dynamic system to disturbances, it is necessary to reduce the stiffness coefficient of the tires of the front wheels. In practice, this is achieved by adjusting the air pressure in the tires. The amplitude-frequency characteristics of the system almost do not change when the damping coefficient of the tires of the front wheels of the tractor is increased in the range from 1 to 3 kN·s/m, while the phase-frequency characteristics improve. This is especially noticeable at the frequencies of oscillations of the disturbing influence in the range of 0–10 s-1. The results could be used as a basis for evaluating the efficiency of tractors with a front plow without a support wheel in tillage operations. Such efficiency can be achieved under the condition of practical implementation of the recommendations proposed in this paper regarding the selection of design parameters of tires for the front wheels of the tractor
Визначення вертикальних коливань трактора з переднім плугом без опорного колеса.
Keywords: plow unit; front attachment mechanism; "push-pull"; front plow; tire stiffness coefficient; tire damping coefficient; орний агрегат; передній навісний механізм; «push-pull»; фронтальний плуг; коефіцієнт жорсткості шин; коефіцієнта демпфування шин